The Relationship between Impulse Buying and Post Purchase Regret in Female Students Who Shop on E-Commerce - Aprilia, Aprilia; Darmayanti, Kusumasari Kartika Hima (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2023)
Research suggests that post purchase regrets are associated with impulse buying. Therefore, this study aims to find out the relationship between impulse buying with post-purchase regrets in students. Sampling in this study is carried out with probability sampling with simple random sampling technique. The participant in this study was an active S1 student at the Islamic State University of Raden Fatah Palembang (n = 340). The data collected was correlated with Pearson Correlation Product Moment analysis techniques using Statistical Packages for Social Science (SPSS) version 23. The results showed that there is a significant positive relationship between impulse buying with post-purchase regret (rxy = 0.472 p = 0,000). This indicates that the higher impulse buying will follow the higher post purchase regret and vice versa. The findings gave the researchers the opportunity to subsequently provide interventions related to impulse buying in order to reduce the post purchase regret.